2003
DOI: 10.1002/eji.200324260
|View full text |Cite
|
Sign up to set email alerts
|

An interaction between CD16 and CR3 enhances iC3b binding to CR3 but is lost during differentiation of monocytes into dendritic cells

Abstract: The receptor for the iC3b fragment of complement, CR3, is involved in monocytes/macrophages and neutrophils phagocytosis. CR3 is known to interact with the low affinity receptor for Ig (CD16) and previous studies have suggested that this cooperation modulates CR3 functions. Herein we have studied the effect of CD16 on the ability of human monocytes CR3 to bind to iC3b. We show that iC3b binding to CR3 is inhibited by several reagents that are known to dissociate the CD16/CR3 complex. In addition, treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…These data, including our own, have mostly been generated using artificial means of activating CR3 to model the presumed effects of iC3b opsonized apoptotic cells binding to the receptor. Data examining the role of iC3b/CR3 interactions in the phagocytosis of apoptotic cells is conflicting (10,(12)(13)(14). In this report, we provide evidence suggesting that CR3 is not necessary for either apoptotic cell phagocytosis or apoptotic cell mediated DC cytokine suppression.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These data, including our own, have mostly been generated using artificial means of activating CR3 to model the presumed effects of iC3b opsonized apoptotic cells binding to the receptor. Data examining the role of iC3b/CR3 interactions in the phagocytosis of apoptotic cells is conflicting (10,(12)(13)(14). In this report, we provide evidence suggesting that CR3 is not necessary for either apoptotic cell phagocytosis or apoptotic cell mediated DC cytokine suppression.…”
Section: Discussionmentioning
confidence: 62%
“…In vitro studies of serum opsonization have been limited to phagocytosis (10,(12)(13)(14) and offer conflicting reports. Apoptotic cells in serum-free conditions have been recently been shown to be equally effective as apoptotic cells with serum opsonins in their ability to inhibit LPS induced IL-12 (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preynat-Seauve et al investigated the possible cross talk between Fc␥RIII, the low affinity receptor for IgG, and CR3 [59]. They found that the interaction of these receptors enhances iC3b binding to monocyte CR3 but the cooperation between CD16 and CR3 is lost during differentiation of monocytes into DCs.…”
Section: Role Of Fcγrsmentioning
confidence: 98%
“…The C3bi moiety incorporated into IC binds to CR3 (Mac-1, CD11b/CD18, ␣ M ␤ 2 integrin) and drives the immune load from Fc␥R to CR3, thus promoting phagocytosis by monocytes in the absence of inflammatory response. Notably, productive binding of C3bi to leukocyte-expressed CR3 needs an interaction with Fc␥RIII to form a CR3/Fc␥RIII complex, the formation of which is impeded in DC (57). DC show a high expression of CD11c, i.e., the ␣-chain of CR4, another integrin with C3bi-binding properties.…”
Section: Discussionmentioning
confidence: 99%